KONSTELASI EKONOMI ISLAM PELUANG DAN TANTANGAN DI ERA GLOBALISASI - Sufyati HS (Himmah: Jurnal Kajian Islam Kontemporer, 2018)
Islamic economy is an economic system that stand on the principle of justice, where sharedprofits and welfare, not personal gain, are the main goal. In the Islamic economic system, theprinciples are: first, getting down to the economy is to meet basic needs in order to worshipand to thank Allah SWT; second, setting the real sector in motion to get the currency incirculation so that no one would be able to accumulate wealth as much as they wish. Thephenomenon of Islamic economic revival in the era of globalization plays a very important rolein dealing with the global economic and financial crisis. The government as a regulator has animportant to achieve the goals of Islamic economy. The goal is falah, which can be achievedthrough maslahah optimization. Therefore, with mandate from Allah SWT and the community,the government’s role in general is to bring what is good for the whole community. There is aneed to observe a number of driving factors behind the Islamic economy revival in the era ofglobalization. The first driving factor is the people’s awareness. The ummah plays double rolesas object and subjec of Islamic economy development. Second, human resources, in term ofquantity and quality. Three qualifications of human resources are required to set the Islamiceconomy in motion. They are kafa’ah (expertise), himmah (work ethics) and amanah(trustworthy). Third, self-reliance of the ummah, that is, the need to change the mindset ofMuslims in regard to Islam with sharia values. Fourth, the need for an institutionand support,complete and conducive system. Fifth, the role and government policy in the development ofIslamic economic system, the support of People’s House of Representatives [DPR] areimmensely important. The government agencies and legislative institution cooperate withofficials in working for the National Sharia Council / DSN-MUI.Keywords: Islamic economy, globalization, syaria bank, Indonesia, policy.